Green synthesis of nanoparticles in cocos nucifera pollen extract using aluminium nitrate nanohydrate with biomedical application and food preservative container - Yuvaraj Tamilselvi; Moorthy Muruganandham; Kanagasabapathy Sivasubramanian; Dhakshan Prakash Vijayalakshmi; Tamilselvan Amirthalingam; Daram Sairam Reddy; Avula Madhav; Jeyanthi Rebecca; Poorni Santhana Krishnan; Sivanraju Rajkumar; Palanivel Velmurugan (Discover Nano)
Abstract Green nanoparticle synthesis, which avoids the use of hazardous chemicals, offers a sustainable alternative to traditional techniques. The purpose of this study was to create aluminium oxide nanoparticles (Al2O3 NPs) by utilizing pollen extract from Cocos nucifera and aluminium nitrate nanohydrate. The spherical shape of the nanoparticles, which ranged in size from 10 to 100 nm and had a prominent absorption peak at 281 nm, was shown by characterization using ultraviolet-visible spectroscopy (UV-Vis), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and High-resolution transmission electron microscopy (HRTEM). The existence of biomolecules that served as capping and reducing agents was verified by FTIR. An IC₅₀ of 43.17% indicated that the produced Al2O3 NPs had considerable antioxidant activity. MIC (Minimum Inhibitory Concentration) and MBC (Minimum Bactericidal Concentration) values of 0.625 mg/mL were found in antibacterial experiments, which demonstrated considerable inhibition zones against E. coli (up to 21 mm) and S. aureus (up to 16 mm). E coli and S. aureus biofilm formation was reduced by 72.46% and 48.55%, respectively, by the nanoparticles. The food-grade covered containers maintained their antibacterial properties even after being cleaned, suggesting that they could be used as environmentally beneficial food preservatives. This work emphasizes how green-synthesised Al2O3 NPs can be used in environmentally friendly food packaging. The long-term performance and safety under actual storage circumstances should be the main topics of future research.